Steel pickling rinse wastewater treatment by two-stage MABR system: Reactor performance, extracellular polymeric substances (EPS) and microbial community. (July 2022) - Sun, Zhiye; Li, Yi; Li, Ming; Wang, Ning; Liu, Jun; Guo, Hong; Li, Baoan
Abstract: A bench-scale two-stage membrane-aerated biofilm reactor (MABR) system was applied to treat steel pickling rinse wastewater with high salinity and refractory organic. The effects of salinity and aeration pressure on the treatment efficiency, extracellular polymeric substances (EPS) characteristics and microbial community structure were studied. The optimal removal efficiencies of COD, NH+ 4-N and TN reached to 62.84%, 99.57% and 51.65%, respectively. Shortcut nitrification was achieved at low aeration, and the salinity less than 4% did not remarkable affect system performance. Colorimetric determination, three-dimensional exaction-emission matrix (3D-EEM) and Fourier transform infrared spectrum (FTIR) were employed to characterize the content and composition of proteins (PN) and polysaccharides (PS) in EPS of the biofilm. The results indicated that PN, not PS, response to changes of environmental conditions played a key role. Moreover, EPS might alleviate intracellular and extracellular osmotic pressure imbalance induced by high salinity, which imparted the biofilm in MABR with prominent salt-tolerant. High-throughput sequencing displayed that nitrifiers ( Nitrosomonas, Nitrospira ), denitrifiers ( Dechloromonas, Hyphomicrobium, Denitromonas, Denitratisoma, Candidatus_Competibacter ) and aerobic denitrifiers ( Pseudomonas, Thauera ) were predominant salt-tolerant bacteria. Graphical abstract: Image 1 Highlights: The two-stage MABR system showed remarkable treatment performance and salt tolerance in steel pickling rinse wastewater treatment. Shortcut nitrification was achieved at low aeration. PN rather than PS in EPS played a key role in response against environmental stress. Proteobacteria and Bacteroidetes were predominant functional bacteria in the biofilm.